Investigation of Correlation between Organizational Commitment and Perceptions of Caring Behavior from the Perspective of Nurses: A Cross-Sectional Study - Naval Heydari; Mahya Torkaman; Camellia Torabizadeh (Preventive Care in Nursing and Midwifery Journal, 2022)
Background: Caring has been introduced as the essence and central value of nursing. One of the factors influencing holistic care is organizational commitment. Objectives: This study aimed to investigate the relationship between organizational commitment and perceptions of caring behavior from the perspective of nurses. Methods: This descriptive correlational study was performed in hospitals affiliated to Shiraz University of Medical Sciences, Fars, Iran, in 2019. The sample size was 210 nurses working in public wards who were randomly included in the study. The data were collected by two standard questionnaires, namely Allen and Meyer Organizational Commitment and Watson Perceptions of Caring Behaviors. The data were analyzed by Pearson correlation coefficient, independent t-test, by SPSS 25. Results: The results showed that the mean (SD) value of organizational commitment of the nurses in this study was 95.30(16.54) at a high level. Additionally, the mean (SD) score of perceiving caring behavior was 142.49(10.71) at a relatively desirable level. There was also a direct and significant relationship between organizational commitment and perceptions of caring behavior (P=0.03; r=0.149). Conclusion: The results of this study indicate a positive relationship between organizational commitment and perceptions of caring behavior. The findings of the present study can help nursing managers and policymakers provide the infrastructure of proper human resource management in the health system and plan to improve the dimensions of organizational commitment and perceptions of nursing caring behavior.